DEVELOPING PORTFOLIO AS AN ALTERNATIVE TESTING DEVICE IN DESCRIPTIVE TEXT WRITING (Journal of Research and Educational Research Evaluation, 2013)
The study on developing portfolio as an alternative testing device in descriptive text writing aims at (1) identifying the problems in using a model of test in descriptive text writing, (2) identifying the suitable model of test in descriptive text writing, (3) describing the model of developing portfolio as an alternative testing device in descriptive text writing, and d) finding out the effectiveness of the use of the model of alternative testing device in descriptive text writing. The research design that used was R&D model adopted from Borg & Gall (1987). There were two instruments used questionnaires and portfolio model in descriptive text writing. The second year students of English study program of Timor University were purposed as the samples with 30 students. The writer used qualitative and quantitative methods to analyze and describe the data. The findings showed that the students still have problems in constructing phrases, constructing sentences, constructing paragraph and writing a descriptive text. They also have problems in the aspects of writing when they are writing. Those problems are how to develop ideas, use good grammar, choose appropriate vocabulary, manage good organization of writing and use good mechanism of writing.